The Effectiveness of Technology Development Towards Walmart’s Sustainability Supply Chain Management - Marylin Winata; Lena Ellitan (CV. ULIL ALBAB CORP, 2023)
This study was conducted to find out about the effectivity of technology towards Walmart’s sustainability supply chain management to handle difficulty in forecasting customers’ demand which led to oversupply issue in August 2022. Aside from sustainability supply chain management, the research also focused on the strategic fit and competitive advantage as well as the company’s supply chain performance and the drivers of it. The research used a secondary data collection method by using media analysis and literature review from existing journals. The results showed that the use of technology has positive impacts towards Walmart’s sustainability supply chain management.